Using of the effect of acoustic emission for determination of hydrogen content in metal melts and alloys - V. B. Vorontsov (Литьë и металлургия)
There is examined the possibility of method preparation of hydrogen content determination in aluminum alloys on the basis of acoustic emission effect.